East Germany's Wage Gap: A non-parametric decomposition based on establishment characteristics - Bernd Görzig; Martin Gornig; Axel Werwatz (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
East German wages have been below the West German wage level since unification. Moreover, the East-West wage gap implied by the contractual wages specified in collective wage agreements is drifting ever further apart from the wage gap in terms of effective wages. This paper looks at the role of establishment-specific factors – such as sectoral affiliation and size of the labour force – in this process. A non-parametric decomposition that has played a prominent role in the gender wage-gap literature is applied to breakdown the East-West wage gap into its constituent components. Using establishment data from the German employment statistics, the paper demonstrates that the divergence between wage agreements and effective wages is probably not a consequence of a massive escape from collective wage agreements, or the intense use of opt-out clauses in such agreements in East Germany. Rather, the shift of East Germany?s economic structure towards lower-paying types of companies has caused the lagging behind in the adjustment of wages.
Keywords: 330